(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
From the analysis of some place-names and ethnic-names of the Western areas of the Iberian Peninsula, which appear in literary and epigraphic documents, the usefulness of comparing both types of sources is established. In the first place, several specific problems of a linguistic nature, such as the fixation of some onomastic forms and the flexion of some names are discussed. Second, taking into account several historical and cultural considerations which derive directly from the problems discussed in the first section, I suggest reconsidering the localization of the forms analyzed. Finally, some relations between these forms and some modern place-names are established as to offer additional support to the thesis defended here.